Subject, Mode and Content in “We-Intentions” - Michael Wilby (Rosenberg & Sellier, 2016)
Propositional attitudes compose of three factors: subject, mode and content. With collective propositional attitudes there is dispute as to which of these three factors the collectivity aspect attaches to. For Searle the collectivity aspect comes in with the mode of the propositional attitude – it is a matter of two distinct individuals each having their own collective intention-in-action. I argue that there are ineliminable difficulties with the Searle’s individualistic analysis, and argue instead for the notion of a dual-subject mental state: a propositional attitude that, by its nature, takes two or more subjects.